Pengaruh Lingkungan Kerja, Motivasi Kerja, dan Kompensasi terhadap Produktivitas Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi - Muhammad Reza Maulid Firdaus Firdaus (GLOBAL SCIENTS PUBLISHER, 2026)
Optimal performance is not only influenced by individual abilities, but also by various organizational factors that support work implementation. These factors include the work environment, work motivation, and compensation provided by the company. In addition, job satisfaction plays an important role in encouraging employees to deliver their best performance. A comfortable and conducive work environment can create a supportive atmosphere that enhances employee productivity. Good physical and non-physical working conditions make employees feel safe and comfortable at work. Meanwhile, work motivation serves as both an internal and external drive that influences employees’ enthusiasm in carrying out their duties and responsibilities. High work motivation encourages employees to work harder and focus on achieving optimal work outcomes. Besides the work environment and work motivation, compensation is another important factor affecting employee performance. Fair and appropriate compensation can increase employees’ morale and loyalty to the company. On the other hand, inappropriate compensation may lead to job dissatisfaction, which can negatively affect employee performance. Therefore, companies need to pay close attention to compensation systems as an effort to improve employee performance. This study aims to analyze the effect of the work environment, work motivation, and compensation on employee performance, with job satisfaction as a mediating variable. This research uses a quantitative method with data collected through questionnaires. The population of this study consists of employees at the company used as the research object, with the sampling technique determined based on specific criteria. The data were analyzed using statistical analysis to examine both direct and indirect effects among variables. The results of this study are expected to provide both theoretical and practical contributions. Theoretically, this research is expected to enrich the field of human resource management, particularly related to factors influencing employee performance. Practically, the findings are expected to serve as a reference for company management in improving employee performance through the improvement of the work environment, enhancement of work motivation, and implementation of fair compensation systems by considering employee job satisfaction.